Artificial intelligence-enhanced quantum chemical method with broad applicability - Peikun Zheng (Nature Portfolio, 2021)
Artificial intelligence is combined with quantum mechanics to break the limitations of traditional methods and create a new general-purpose method for computational chemistry simulations with high accuracy, speed and transferability.